2020
DOI: 10.3390/ijerph17176330
|View full text |Cite
|
Sign up to set email alerts
|

Information on the COVID-19 Pandemic in Daily Newspapers’ Front Pages: Case Study of Spain and Italy

Abstract: Spain and Italy are amongst the European countries where the COVID-19 pandemic has produced its major impact and where lockdown measures have been the harshest. This research aims at understanding how the corona crisis has been represented in Spanish and Italian media, focusing on reference newspapers. The study analyzes 72 front pages of El País and El Mundo in Spain and Italy’s Corriere della Sera and La Repubblica, collecting 710 news items and 3456 data evidences employing a mixed method (both qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 21 publications
3
35
0
8
Order By: Relevance
“…However, there are unknown factors in the transmission of the disease, in addition to oral droplets and infectious agents, coupled with a high risk of death after infection [ 17 , 18 ]. At the same time, the follow-up media reports emphasize the severity of the global epidemic and reinforce fear in people’s minds [ 19 ]. Therefore, it is difficult to change people’s travel expectations in the short term [ 6 ], resulting in a significant decrease in the number of Taiwanese travelers entering and leaving the country [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are unknown factors in the transmission of the disease, in addition to oral droplets and infectious agents, coupled with a high risk of death after infection [ 17 , 18 ]. At the same time, the follow-up media reports emphasize the severity of the global epidemic and reinforce fear in people’s minds [ 19 ]. Therefore, it is difficult to change people’s travel expectations in the short term [ 6 ], resulting in a significant decrease in the number of Taiwanese travelers entering and leaving the country [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the pandemic as a result of COVID-19 has been one of the most serious situations for humanity [ 1 ] In Spain, the incidence of COVID-19 has been particularly complex with a high number of people affected and a high mortality rate [ 2 ]. The serious consequences produced by the disease imply people requiring hospitalization and special care [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, there has been research on the adoption of social media by world leaders ( Barberá and Zeitzoff, 2018 ). Also, it is important to examine communication on Twitter by political leaders as the research on daily newspapers in Spain and Italy has shown that the protagonists of the pandemic are especially politicians ( Tejedor et al., 2020 ). The research on the usage of Twitter during the COVID-19 pandemic is ongoing, but there have been already several studies analyzing the impact of COVID-19 on Twitter usage.…”
Section: Introductionmentioning
confidence: 99%